A study on the use of capital budgeting to support investment decisions in Iceland - Kári Jóhannsson 1976- (2017)
How do Icelandic companies, regularly faced with investment decisions, use capital budgeting methods & theories to support their investment decision making? This question has now been studied using case studies and in-depth interviews, adding a new market and a qualitative approach to this international research subject. Although the sample is small the results fit into the results of comparable quantitative studies. As with other markets, the usage is mainly controlled by the size of companies, although Icelandic companies do not hesitate to use the more sophisticated methods, despite the lack of input information that is common on emerging capital markets like Iceland. This research project studies the how and why of how certain capital budgeting methods are used, and is intended to be informative to businesses that want to see what others are doing and improve their own usage. In addition to answering the research questions, a research based usage proposition is generated out of this project. Keywords: Capital Budgeting; Corporate Finance; Investment decisions; Case Study; Emerging Markets; Iceland